PERANCANGAN SISTEM PENGADUAN MASYARAKAT (SIPADU) DENGAN RAD UNTUK PENINGKATAN PELAYANAN PUBLIK DI KALANGDOSARI: DESIGN OF A PUBLIC COMPLAINT SYSTEM (SIPADU) WITH RAD TO IMPROVE PUBLIC SERVICES IN KALANGDOSARI - Dzanuar wildan; Saifur Rohman Cholil (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Public services at the village level often struggle with issues of efficiency and transparency due to outdated manual complaint systems. In Kalangdosari Village, having a digital platform that enables communication between residents and village officials is crucial for enhancing service quality. This study aims to design and create a web-based Community Complaint System (SIPADU) that can manage reports from the public in an integrated, transparent, and accountable manner. The method chosen for system development is Rapid Application Development (RAD), which allows for the quick and flexible creation of software through iterative cycles. System evaluation is conducted using two methods: Black Box Testing to verify technical functions and the System Usability Scale (SUS) to assess user satisfaction and experience. Test results indicate that all functional features of the SIPADU system operate according to technical specifications without failures. Usability testing revealed that the system is deemed acceptable (Acceptable) with a good rating (Good), indicating that the system's interface is easy for both village residents and administrators to understand and use. The implementation of SIPADU in Kalangdosari Village has proven effective in digitizing the complaint process and provides a RAD-based development framework that can be used in other villages. This research contributes to the utilization of information technology to enhance more responsive and modern village governance.